Pengaruh Masa Kerja, Lingkungan Kerja dan Kepuasan Kerja Terhadap Produktivitas Tenaga Penyuluh Lingkungan Keluarga Berencana (PLKB) di Kabupaten Madiun - Qori Anjani Putri; Ninik Srijani; Dwi Nila Andriani (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2023)
This research aims to: (1) determine the effect of work period on work productivity, (2) determine the effect of work environment on work productivity, (3) determine the effect of job satisfaction on work productivity, (4) determine the effect of work period, work environment, and job satisfaction work on work productivity. This research method is included in quantitative research with comparative causal research. The sampling technique used is the sample population where the entire population is sampled. The population in this study were all Family Planning Environmental Extension Officers (PLKB) in Madiun Regency, totaling 46 PNS employees and 6 non-PNS employees with a total of 56 employees where all of these employees would be the sample in this study. Data were analyzed using variable test, prerequisite test, and hypothesis test. The results of this study indicate that (1) partially there is a positive and significant influence between tenure on work productivity 9,8, (2) partially there is a positive and significant effect between work environment on work productivity 9,7, (3) partially there is a positive and significant influence between job satisfaction on work productivity 3,1, (4) it can be concluded that partially there is a positive and significant influence between tenure, work environment, and job satisfaction on work productivity.